2018
DOI: 10.3390/s18061920
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis Method for a Mine Hoist in the Internet of Things Environment

Abstract: To reduce the difficulty of acquiring and transmitting data in mining hoist fault diagnosis systems and to mitigate the low efficiency and unreasonable reasoning process problems, a fault diagnosis method for mine hoisting equipment based on the Internet of Things (IoT) is proposed in this study. The IoT requires three basic architectural layers: a perception layer, network layer, and application layer. In the perception layer, we designed a collaborative acquisition system based on the ZigBee short distance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The study revealed that knowledge of environmental conditions could help prevent errors during the design phase in additive manufacturing. Li et al utilized IoT sensors to collect data for the fault diagnosis of mine hoisting equipment [ 13 ]. The study revealed that IoT sensors can help provide complete diagnosis data as well as improve diagnosis results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed that knowledge of environmental conditions could help prevent errors during the design phase in additive manufacturing. Li et al utilized IoT sensors to collect data for the fault diagnosis of mine hoisting equipment [ 13 ]. The study revealed that IoT sensors can help provide complete diagnosis data as well as improve diagnosis results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent technologies such as Internet of Things (IoT)-based sensors can be utilized and integrated with monitoring systems. Studies have been conducted in the manufacturing industry and showed significant benefits from the use of IoT-based sensors for monitoring such as working condition improvements [ 11 ], error design prevention [ 12 ], fault diagnosis [ 13 ], quality prediction [ 14 ], and helping managers with better decision making [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the implementation of the access network part, the GPRS module of the GPRS232-7S2 model is used as the gateway of the LoRa network, which is communicated with the microcontroller through the UART (universal asynchronous receiver/transmitter) port [36,37]. A power distribution room is responsible for the power supply of three adjacent brine pumps, and from the middle of the brine pump closer.…”
Section: Realization Of Information Acquisition and Transmissionmentioning
confidence: 99%
“…In recent years, in order to monitor the states of the electrical drive system of the hoist in real time and provide timely maintenance advice to avoid unnecessary disasters and losses, scholars have studied the fault diagnosis of the hoist, mainly researching the diagnosis technologies of the hoist and its corresponding critical equipment. Using the Internet of Things to diagnose the fault of the hoist and basing on the improved Dezert-Smarandache theory, fault diagnosis reasoning can be performed and remote data transmission and fault diagnosis can be achieved (Li, Xie, et al, 2018). Based on the proposed new MMC modular multilevel converter, the change of the measuring point voltage was obtained by changing the output terminal voltage, and the open and short circuit faults were detected (Haghnazari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%